2021
DOI: 10.3389/fendo.2021.721813
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sex Hormone Receptor and Immune Response Genes in Peripheral Blood Mononuclear Cells During the Menstrual Cycle

Abstract: Sex hormones are known to interact with the immune system on multiple levels but information on the types of sex hormone receptors (SHR) and their expression levels in immune cells is scarce. Estrogen, testosterone and progesterone are all considered to interact with the immune system through their respective cell receptors (ERα and ERβ including the splice variant ERβ2, AR and PGR). In this study expression levels of SHR genes in peripheral blood mononuclear cells (PBMCs) and cell subsets (CD4+ and CD8+ T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…49 The expressions of several immune response genes in human PBMCs including GATA3, IFNG, IL1B, LTA, NFKB1, PDCD1, STAT3, STAT5A, TBX21, TGFB1, TNFA changes during menstrual cycle. 50 In this present study, we showed that many immune response genes were highly expressed in women, along with many immune response signaling pathways. Furthermore, we showed from ML analysis that many immune response genes like IFITM2 and IFITM3, or IL32 are important to separate CAD vs non-CAD in female.…”
Section: Discussionsupporting
confidence: 48%
“…49 The expressions of several immune response genes in human PBMCs including GATA3, IFNG, IL1B, LTA, NFKB1, PDCD1, STAT3, STAT5A, TBX21, TGFB1, TNFA changes during menstrual cycle. 50 In this present study, we showed that many immune response genes were highly expressed in women, along with many immune response signaling pathways. Furthermore, we showed from ML analysis that many immune response genes like IFITM2 and IFITM3, or IL32 are important to separate CAD vs non-CAD in female.…”
Section: Discussionsupporting
confidence: 48%
“…Analysis of PBMCs has revealed significant changes in gene expressions, including that of TNF superfamily member 14 and signal regulatory protein-γ, during the menstrual cycle of patients with SLE compared to that of HCs ( 72 ). A study analyzing the expression of sex hormone receptor genes in PBMCs, and cell subsets reported that several immune response genes were more highly expressed during the ovulatory and mid-luteal phase ( 73 ). In addition, the level of sex hormone-binding globulin, a steroid hormone transport protein, was correlated with ERβ1 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to this, Brundin et al have shown an upregulation of genes associated with NF‐κB signaling in peripheral blood monocytes in the luteal phase. Noteworthy, however, is the finding that genes associated with both Th1 and Th2 cytokine responses were upregulated in the luteal phase compared to the follicular phase, therefore suggesting a differential regulation between cycle phases but not one separated into either pro−/anti‐inflammatory or Th1/Th2 response 206 . This suggests that it may be too simplistic to break down the actions of estrogen and progesterone or the different menstrual cycle phases into either pro‐ or anti‐inflammatory categories, as immune responses are regulated by a complex network of stimulatory and inhibitory pathways in multiple cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, however, is the finding that genes associated with both Th1 and Th2 cytokine responses were upregulated in the luteal phase compared to the follicular phase, therefore suggesting a differential regulation between cycle phases but not one separated into either pro−/anti-inflammatory or Th1/ Th2 response. 206 This suggests that it may be too simplistic to break down the actions of estrogen and progesterone or the different menstrual cycle phases into either pro-or anti-inflammatory categories, as immune responses are regulated by a complex network of stimulatory and inhibitory pathways in multiple cell populations. Therefore, we would encourage future research investigating inflammatory processes to focus more on individual regulatory networks rather than aiming to categorize effects.…”
Section: Cytokines and Their Release From Immune Cellsmentioning
confidence: 99%